Evaluating Traditional Chinese Medicine and Herbal Products for the Treatment of Gestational Diabetes Mellitus - Yang Xin Zi Xu; Shengyan Xi; Xiaoyan Qian (Journal of Diabetes Research)
Gestational diabetes mellitus is the most common metabolic disorder during pregnancy with health consequences for both lives during and after pregnancy. Studies found that many pregnant women turn to complementary and alternative medicine for health maintenance or symptom relief, such as herbal medicine and acupuncture from traditional Chinese medicine. With the growing popularity of traditional Chinese medicine, we conducted a systemic search in PubMed, Web of Science, and Embase databases on research studies that investigated traditional Chinese medicine during pregnancy. The resultant hits were further searched in relation to all diabetes mellitus. In total, we found three major herbal medicine/herbal products that were associated with glycemic control in gestational diabetes, including Zuo Gui Wan, red raspberry leaves, and Orthosiphon stamineus. We further reviewed them and their relatives in relation to type 2 diabetes mellitus and found more evidence of metabolic benefits. None of the herbal medicine and products examined reported toxicity in the experimental models. Overall, treatments of gestational diabetes by western or alternative interventions are grossly understudied. It is critical to have a standardized protocol when evaluating efficacy of herbal medicine and produce quality results for women and their health-care providers to make informed treatment decisions.